Rethinking Mentoring: Comparing Policy and Practice in Special and General Education - Wasburn-Moses, Leah (Education Policy Analysis Archives, 2010)
Although teacher mentoring is now mandated in most states, high quality research in mentoring remains scarce (Rockoff, 2008). There is a great need to understand how such policies are implemented (Smith, 2007), particularly in teaching areas with high shortages. The purpose of this study is to compare state and district mentoring policies with the mentoring experiences of practicing special and general education teachers. Survey data were collected from 232 teachers in one state and compared with policy information from the Teacher Rules, Roles, and Rights (TR3) database. Results indicated uneven implementation of policy, in that some stated policy was not adhered to consistently, and consistency in practices was seen in the absence of other policy. Further, special education teachers reported much less mentoring than general education teachers. A new model is proposed to encourage implementation of research-validated practices in teacher mentoring.